Subcutaneous versus intravenous trastuzumab for HER2-positive breast cancer: a global systematic review and meta-analysis with a cost-minimization analysis from the Chinese healthcare system perspective - Zeng, Zheng; Zhong, Li; Zhu, Ling; Liao, Luqin; Zhu, Zefeng; Cao, Yuening; Zheng, Da; Huang, Guidong; Chen, Wei; Zhang, Lin (Frontiers in Pharmacology, 2026)
BackgroundSubcutaneous (SC) trastuzumab offers a more convenient alternative to intravenous (IV) administration for HER2-positive breast cancer, potentially improving healthcare efficiency and patient experience. Although SC trastuzumab was approved in Europe in 2013 and in the United States in 2019, it only became available in China in 2022, highlighting the need to synthesize global evidence for regions where SC adoption is recent.MethodsA systematic search of PubMed, Embase, Web of Science, and the Cochrane Library through 20 March 2025, identified studies comparing SC and IV trastuzumab. Meta-analyses were performed using random- or fixed-effects models to evaluate pathological complete response (pCR), event-free survival (EFS), adverse events, serious adverse events, and patient preference. A cost-minimization analysis (CMA) was additionally performed from the perspective of the Chinese healthcare system.ResultsNine studies were included. SC trastuzumab demonstrated comparable pCR (OR = 1.11, 95% CI: 0.86–1.42) and EFS (HR = 0.96, 95% CI: 0.78–1.19) to IV administration. SC was associated with a higher incidence of mild-to-moderate local reactions (OR = 1.59, 95% CI: 1.38–1.84) but no significant difference in serious adverse events (OR = 1.37, 95% CI: 0.94–1.99). Patient preference strongly favored SC (OR = 63.02, 95% CI: 34.43–115.34). Cost-minimization analysis showed that 18 cycles of SC trastuzumab (100,597 CNY) reduced costs by approximately 7% compared with the IV originator (108,032 CNY) and were generally comparable to domestic biosimilars, which ranged from 79,432 to 101,817 CNY.ConclusionSC trastuzumab demonstrates comparable clinical outcomes to IV administration, with a marked patient preference advantage and potential cost savings compared with the IV originator and domestic biosimilars. These findings are particularly relevant to healthcare systems where SC formulations are newly introduced, providing timely evidence to guide patient-centered clinical decision-making.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=637674, identifier CRD42025637674.